UV-B irradiation effects on pigments and cytological behaviour of callus in sainfoin (Onobrychis viciifolia Scop.) - Mohajer, Sadegh; Taha, Rosna Mat; Mohajer, Minoo; Anuar, Nordiyanah (Emerald, 2018)
Purpose: This study aims to determine the appropriate irradiation dose for induction of somaclonal variation in mass of unorganized parenchyma cells derived from sainfoin (Onobrychis viciifolia) tissues. Design/methodology/approach: To investigate the feasibility of UV-B irradiation (312 nm), seeds and callus of sainfoin were exposed to five different intensities (20-100 per cent) for evaluating the effectiveness of phytochemical constituents and cellular behaviour. Findings: Although percentage of seed viability reduced in 20 per cent intensity of UV-B irradiation compared with control seeds, the germination speed significantly enhanced from 3.58 to 5.42. The spectrophotometer analysis confirmed that concentrations of chlorophyll (a and b) decreased after UV-B exposure as compared with control callus. Also, carotenoid content showed significant differences among treated calli. Flavonoid and phenolic contents were observed to gradually increase when the non-irradiated callus subjected to 40 and 60 per cent intensities of UV-B irradiation, respectively. Observation on cellular behaviour such as determination of nuclear and cell areas, mitotic index and chromosomal aberrations were also detected to change in different intensities of UV-B irradiation. Fragmented and aneuploidy aberrations were only observed in exposed cells with more than 40 per cent intensity of UV-B irradiation. Originality/value: In reality, radiocytological evaluation was proven to be essential in deducing the effectiveness of UV-B irradiation to induce somaclonal variation in callus tissue of sainfoin.